PENGARUH FREKUENSI PERDAGANGAN SAHAM DAN TRADING VOLUME ACTIVITY TERHADAP BID ASK SPREAD DENGAN RETURN SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 DI BURSA EFEK INDONESIA TAHUN 2017 – 2020 - Windiana, Dina; Arief, Mohammad Yahya; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Invesment is a commitment to a number of funds or other resources made at this time, with the aim of obtaining a number of benefits in the future. Investors as actors in every trading activity in the capital market need relevant information in making decisions to carry out trading activities in the capitals market, be it buying, holding or selling the securities the own. The purpose of this study was to analyze and examine the influence of Stock trading frequency and Trading volume activity on Bid ask spread through Stock returns. This research uses quantitative research methods. The population in this study are companies listed in the LQ45 Index with a sample of 9 companies. The sampling technique used was purposive sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS–SEM). The results of the analysis using the Smart Partial Least Square (PLS) 3.0 software, show that of Stock trading frequency has a significant positive effect on Stock returns, Trading volume activity has a negative but not significant effect on Stock returns, Stock trading frequency has a significant positive effect on the Bid ask spread, Trading volume activity has a significant positive effect on the Bid ask spread, Stock return has a significant positive effect on the Bid ask spread. the results of the influential hypothesis that are not immediately pointed to the of Stock trading frequency on the Bid ask spread through Stock returns has a positive but not significant effect, Trading volume activity on the Bid ask spread through Stock returns has a negative but not significant effect.